Adequacy of Tissue Sampling in Breast Specimen. (11th September 2019) - Khawar, Sidrah; Hamza, Ameer; Alrajjal, Ahmed; Salehi, Sajad; Qu, Hong
Abstract: Objectives: Due to inadequate sampling concerns, pathologists frequently request additional tissue sections (ie, more tissue sections in addition to initial representative sections) in breast specimens. This study explores the effectiveness of the additional tissue sections in the breast specimens. Methods: Breast specimens received in our institution on which additional tissue sections were requested were included in the study. Pathology reports and glass slides for these specimens were reviewed. Additional tissue sections were considered effective if they changed the final diagnosis altogether, changed a benign entity to borderline or malignant category, changed pathologic tumor stage, changed margin status, changed tumor focality, or if lymphovascular invasion was identified. Results: A total of 325 specimens were identified. Of these, 98 (30.1%) were benign while 224 (68.9%) were malignant. Among malignant cases, 53 (23.7%) had neoadjuvant therapy. Overall mean initial representative sections submitted were 15.1 ± 8.7 while additional tissue sections were 10.7 ± 8.0. There was no difference in additional sections submitted for benign versus malignant cases (9.8 ± 7.7 vs 11.2 ± 8.0; P = .96). Also there was no difference in additional sections submitted for cases with neoadjuvant therapy versus those without any therapy (10.4 ± 6.9 vs 11.6 ± 8.4; P = .36). Twenty-five (7.7%) specimens benefited from submission of additional tissue sections. All 25 cases were malignant; 7 had neoadjuvant therapy while 18 did not. No tumor was identified in initial representative sections in 6 cases, pathologic tumor stage was changed in 12 cases, margin status changed in 2 cases, tumor focality changed in 4 cases, and an extra positive lymph node was identified in 1 case. Conclusion: Additional tissue sections contributed to final diagnosis in 7.7% cases. Surgical pathology breast specimens require specialized handling and thorough sampling for accurate diagnosis and staging.